Soral synapomorphies are significant for the systematics of the Ustilago-Sporisorium-Macalpinomyces complex (Ustilaginaceae) - McTaggart, A.R. (Nationaal Herbarium Nederland & Centraallbureau voor Schimmelcultures, 2012)
The genera Ustilago, Sporisorium and Macalpinomyces are a polyphyletic complex of plant pathogenic fungi. The four main morphological characters used to define these genera have been considered homoplasious and not useful for resolving the complex. This study re-evaluates character homology and discusses the use of these characters for defining monophyletic groups recovered from a reconstructed phylogeny using four nuclear loci. Generic delimitation of smut fungi based on their hosts is also discussed as a means for identifying genera within this group. Morphological characters and host specificity can be used to circumscribe genera within the Ustilago-Sporisorium-Macalpinomyces complex.